End of summer - Pilcher, Rosamunde (St. Martin's Press)
At the end of the summer, sitting on a California beach, Jane Marsh thinks back to her childhood at the estate called Elvie in a remote corner of Scotland. She remembers not only the heather-covered hills and the lonesome loch but also her grandmother--and, of course Sinclair. She had dreamed of marrying rakishly handsome Sinclair and settling at Elvie forever. Now an urgent visit from her grandmother's lawyer is the catalyst for her return to Scotland, where waiting for her is passion, not gentle love--and the chilling realization that she might be preparing to marry the wrong man
45959
Keywords: Relationships; Scotland; California